PENGARUH KOMUNIKASI KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN PADA STIKES TUANKU TAMBUSAI BANGKINANG - Yanti Yandri Kusuma (Departement of Mathematics Education, 2019)
This research was conducted at STIKes Tuanku Tambusai Bangkinang which is located on street of Lenan Boyak No.69 Bangkinang. STIKes Tuanku Tambusai Bangkinang is one of higher education in the field of health problem formulation in this research is whether leadership communication has an effect on employee job satisfaction at STIKes Tuanku Tambusai Bangkinang. The research aims to know how leadership communication to employee job satisfaction at STIKes Tuanku Tambusai Bangkinang. The result of the research shows that in descriptive analysis, leadership communication on Tuanku Tambusai STIkes is categorized either where the employee's response that the leader communicates directly or indirectly is good enough with the amount of job satisfaction response as much as 32 people or 41.6%. While the influence of communication between employee job satisfaction is moderate and positive where the correlation coefficient R = 0.375 meaning leadership communication affect job satisfaction of 37.5% while the remaining 62.5% influenced by other factors not examined in this study.